Long-distance interactions between regulatory elements are suppressed at the end of a terminally deficient chromosome in Drosophila melanogaster. - Melnikova, L.; Biryukova, I.; Kan, T.; Georgiev, P. (Chromosoma, 2008)
In Drosophila melanogaster, broken chromosome ends behave as real telomeres and are believed to be covered with telomere-specific chromatin. It has been shown previously that the telomeric chromatin represses normal activity of enhancers that regulate yellow expression in wings and body cuticle. In this paper, we have found that a modified yellow promoter is fully active in the wing and body cuticle when it is located at the chromosome end, which is evidence that the telomeric chromatin does not repress transcription. Substitution of the yellow core promoter region, including TATA and Inr, with the promoter regions of the eve, hsp70 (TATA-containing), and white (TATA-less) promoters does not affect the ability of the promoter to be cis- or trans-activated by the yellow enhancers if the heterologous promoter is located at a distance of about 6 kb from the chromosome end. The best characterized Drosophila insulator found in the gypsy retrotransposon can specifically repress the yellow promoter at a distance when one component of the insulator complex, Mod(mdg4)-67.2 protein, is inactive. We have also found that, in the mod(mdg4) mutant background, the gypsy insulator can repress the heterologous promoters, indicating that the core promoter elements are not critical for specificity of repression. However, long-distance functional enhancer-promoter and gypsy-promoter interactions were suppressed when the distance between the yellow promoter and the end of the deficient chromosome was less than 6 kb. These results suggest that Drosophila telomeric chromatin does not generally repress transcription but is somehow involved in suppression of some long-distance interactions between regulatory elements.